(untitled) (Journal of Parents and Teachers, 2014)
Television is a vehicle of socialization and knowledge which is undervalued in schools. Watching TV and reading a good book are not exclusive activities. What is undeniable is that television has changed the culture and shaped the last generations of children with good programs ... and not so good.